Comparison of Real Costs against the Price of INA-CBG's Ischemic Stroke in Bethesda Hospital - Muslimah Muslimah; Tri Murti Andayani; Rizaldy Pinzon; Dwi Endarti (Faculty of Pharmacy, Universitas Gadjah Mada)
Stroke is the leading cause of death and disability that includes disability mild, moderate and severe need of maintenance costs high. The purpose of this research is to know the characteristics of the patient, the comparison of real costs and fares INA CBG's ischemic stroke inpatient and outpatient in Bethesda HOSPITAL Yogyakarta. This research was conducted with observational analytic approach with cross sectional design based on the perspective of the hospital. The subject of research that meets the criteria of inclusion as much as 96 patients. Criteria for Inclusion include patient JKN, ischemic stroke of the first offensive, onset of less than 24 hours and non of the references. Observation period 1 October 2015 sd 31 March 2016 inpatients were observed 6 months in retrospective. Secondary data research data are sourced on the medical record, IFRS, and Technology Unit of RS. Analysis of statistical data by the method of Mann Whitney and Kruskal Wallis. Based on the characteristics of long hospitalizations, inpatient class there is significant influence (p < 0.05) against ischemic stroke patients real costs of hospitalization. The total real costs RS ischemic stroke of Rp 993,181,170 to 96 111 patients with inpatient visits so that the cost of Rp 8,947,578 per episode of hospitalization. Furthermore the Total cost of stroke ischemic amounting to Rp 139,165,150 with 211 outpatient visits so that the cost of Rp 659,550 per an outpatient episode. Real costs RS ischemic stroke than outpatient rates INA CBG's-2014 have significant differences. Similarly the real costs of hospitalization compared to price of INA-CBG's 2014 have significant differences in class i. In conclusion Fund fares INA-CBG's either outpatient or inpatient insufficient finance the care of patients ischemic stroke in Bethesda hospital Yogyakarta.